Sago Palm Genome Size Estimation via Real-Time Quantitative PCR - Azman Roslan*, Hairul; Anowar Hossain, Md; Ngui Sing, Ngieng; Husaini, Ahmad (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
Sago palm, Metroxylon sagu Rottb., is an underutilized indigenous food crop that can be found mainly in the South East Asia and Pacific regions. It is a main starch producer and socioeconomically important crop in the South East Asia region including Malaysia. The sago starch provides foronsiderable potential to food security in the places where it is grown. However, not many molecular works have been reported thus far. In the post genomic era, sago plant genome sequencing is very important for sustainable starch development in these regions. Therefore, determination of the genome size is prerequisite to full genome sequencing and assembly. Here we report on the use of real-time quantitative polymerase chain reaction (qPCR) in determining the genome size. For this work, we calculated the genome size, G (bp) of M. sagu based on qPCR-derived copy number of two single copy genes. Pichia pastorisas a control to estimate sago palm genome size. With this technique, the genome size of M. sagu was calculated to be 1.87 Gbp. This genome size information would be beneficial for subsequent molecular work including genome sequencing and analysis on this economically important crop plant. Keywords: Genome size; Metroxylon sagu; real-time PCR; copy number; Pichia pastoris *Corresponding author: Tel.: +60 82 58 3038 Fax: +60 82 58 3160 E-mail: hairulroslan@hotmail.com